User Needs Assessment for Climate Services in Zambia - Clarkson, Graham; Dorward, Peter; Poskitt, Samuel; Mambwe, Dina; Mtonga, Radhia K.; Below, Till (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Between February and April 2021 research was conducted to assess the user needs of selected farmer groups in Zambia for farmer centric agrometeorological information services. Specifically, it aimed to: • Identify the types of weather information and agronomic advice that farmers currently receive, the sources that they use and how satisfied they are with the information they receive; • Better understand the effects of climate variability and change on different agricultural activities and the decisions farmers are able to make; and • Enable farmers to identify what weather and climate information, services and agronomic advice they need and how they would like to access it. The results were then presented to key stakeholders and used in an ideation process to help design potential climate services for implementation at scale. Key findings from the user research are that: • Respondents articulated a demand for information and advice on a range of different weather variables at a range of different timescales to aid both their long- term planning and more immediate decisions. • There is a gap between the climate and weather information and services that are produced (by Zambia Meteorological Department) and those that farmers are accessing. • The complexities of challenges facing respondents, and the variety of different decisions affected, means that addressing these challenges is not simply about the provision of climate information but supporting farmers to contextualise and use this information. Farmers outlined a range of existing practices that they use to address challenges that are related to weather and climate. Many of these practices address multiple challenges and are often proactive rather than reactive options for farmers. • Engaging farmers with climate services requires a range of different and complimentary approaches. Radio is the most commonly used and requested going forward. Extension staff, lead farmers and farmer groups are important sources of information and support in farmer decision making. Climate services products should be designed with the aim to address multiple farmer ‘problems’. For example, information on the amount of rainfall to expect in a season can aid decision making on choice of land preparation and cultivation methods, choice of crop variety, weeding, as well requirements for pest and disease management in cattle.